Investigation of grain boundaries for abnormal grain growth in polycrystalline SrTiO - Shin, S; Lozano-Perez, S; Cockayne, D (2010)
Strontium titanate (SrTiO) is widely used in electronic devices, and it is a model material for understanding the structural and dielectric properties of grain boundaries (GBs). In such materials, the GBs often play a dominant role in sintering and microstructural behavior. Abnormal grain growth (AGG) is a commonly observed phenomenon. Most studies explained that GBs contain continuous liquid films, and this liquid assists interface diffusion resulting in fast growth. However, few studies investigate the AGG behavior without any liquid. In this study, GB morphology and chemistry have been characterized by high-resolution transmission electron microscopy and x-ray energy-dispersive spectrometry, respectively. Different distributions of GB morphology have been observed in abnormal grains and matrix grains, and GB chemistry varies with different morphological type GBs. By correlating GB morphology and chemistry, a possible mechanism for AGG is proposed. © 2010 Materials Research Society.